Theorizing about the epistemic. Issue 7 (16th November 2016) - Cohen, Stewart
Abstract: I argue that epistemologists' use of the term 'epistemic' has led to serious confusion in the discussion of epistemological issues. The source of the problem is that 'epistemic' functions largely as an undefined technical term. I show how this confusion has infected discussions of the nature of epistemic justification, epistemic norms for evidence gathering, and knowledge norms for assertion and belief.